(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
MANET is designed as a self-configuring and organized network of mobile nodes that use wireless links to communicate without relying on a pre-conﬁgured infrastructure or a central base station. Nodes within MANET are free to move autonomously in any direction without any constraints, so MANET has a dynamic topology. Because of its salient characteristics, MANETs are suitable for applications such as military and disaster relief. However, the characteristics of dynamic network topology, lack of infrastructure, and lack of certificate authority make the security issue of MANETs more challenging. Routing protocols in MANETs are numerous, they ensure the routing of data between nodes however they neglect the security aspect. Although the AODV protocol is one of the protocols with certain performance and low overhead making it very suitable for the characteristics of MANETs, it contains certain breaches making it vulnerable to several attacks. A common attack is the black hole attack. This paper presents a mechanism using the time required to generate the RREP packet to detect and prevent malicious nodes from performing a black hole attack. This solution provides better results with less computation and less routing overhead